Affordable housing provision projects in Bali, Indonesia : Improving quality and cultural acceptability - Dwijendra, Ngakan Ketut Acwin (Curtin University, 2014)
This research investigates the significant factors related to affordable housing projects in Bali: cultural appropriateness, developer’s constraints, and dwellers involvement. Data was collected through observations, questionnaires, interviews, focus group discussions and then analyzed qualitatively as basis of discussion and conclusions. The research shows that housing projects are not culturally acceptable. Most constraints of developers are high costs of building materials and labor. Dwellers have no involved and adjusted their houses to be more culturally suitable.Keywords: affordable housing provision, cultural acceptability, developer constraints.